TASHKENT AND FERGANA REGIONAL COSTUME SPECIFIC FEATURES, REGIONAL AND SOCIAL SIGNS IN CLOTHES - K. Fuzailova; U. S. Raxmatullayeva (Journals Park Publishing, 2022)
The article examines the features of the costumes of the Tashkent and Ferghana regions, analyzes the form, fabrics, as well as regional and social characteristics of headdresses, embroidery.